EVALUATING NORMAL GLYCEMIC EFFECT OF STEM EXTRACTS OF ABRUS PRECATORIUS IN STZ-INDUCED DIABETIC WISTAR RATS - Badeggi, Muhammad Hassan; Olalekan, Amuzat Aliyu; Yakubu, Ndatsu (FUDMA JOURNAL OF SCIENCES, 2025)
Diabetes mellitus (DM) is a widespread metabolic disorder, particularly in developing regions where access to effective and affordable treatment remains a challenge. This study evaluated the antidiabetic efficacy, safety, and biochemical impacts of aqueous (AE) and methanolic (ME) extracts of Abrus precatorius stem in streptozotocin (STZ)-induced diabetic Wistar rats. Phytochemical screening revealed the presence of key bioactive compounds, including flavonoids, alkaloids, saponins, tannins, and glycosides. Acute toxicity tests confirmed a high safety margin for both extracts. Diabetic rats treated orally with AE and ME at doses of 100, 200, and 400 mg/kg over 14 days showed significant, dose-dependent reductions in fasting blood glucose levels. The highest doses (400 mg/kg) of both extracts nearly restored glucose levels to those of normal controls, comparable to the standard drug glibenclamide. Additionally, treatment improved lipid profiles by lowering total cholesterol, triglycerides, and low density lipoprotein (LDL) levels while increasing high density lipoprotein (HDL), with the ME-400 group showing slightly superior effects. Liver enzyme analysis revealed that diabetes-induced elevations in ALT and reductions in AST were modulated by the extracts, indicating hepatoprotective potential. The methanolic extract, likely due to better extraction of nonpolar bioactives, demonstrated slightly more pronounced therapeutic effects across biochemical parameters. These findings suggest that Abrus precatorius stem extracts, particularly at higher doses, exhibit potent antihyperglycemic, lipid-lowering, and hepatoprotective properties. Therefore, this result supports their potential use as safe, effective, natural and accessible therapeutic agents in the management of diabetes mellitus especially in low-resource healthcare settings.
Keywords: Diabetes mellitus; Abrus precatorius; Streptozotocin; Phytochemicals; Aqueous and methanolic extracts